The Olfactory Receptor Family 2, Subfamily T, Member 6 (OR2T6) Is Involved in Breast Cancer Progression via Initiating Epithelial-Mesenchymal Transition and MAPK/ERK Pathway - Li, Ming; Wang, Xiao; Ma, Ran-Ran; Shi, Duan-Bo; Wang, Ya-Wen; Li, Xiao-Mei; He, Jun-Yi; Wang, Jun; Gao, Peng (Frontiers in Oncology, 2019)
Breast cancer is the most common female malignancy in the world, however its molecular pathogenesis still needs in-depth investigation. Here we first revealed that OR2T6, which belongs to the olfactory receptor (OR) family, was over-expressed in breast cancer tissues compared with normal breast tissues (p<0.05). OR2T6 expression was tightly correlated with higher TNM staging and lymph node metastasis (p=0.033 and 0.002 separately), and associated with worse patients’ overall and disease-free survival (p=0.009 and 0.013 separately). In the in vitro level, OR2T6 enhanced the proliferation, invasion and migration ability of breast cancer cell lines (MCF-7 and MDA-MD-231). It promoted the expression of mesenchymal markers (Vimentin, N-cadherin and β-catenin) while inhibits E-cadherin expression. Thus OR2T6 might play a key role in the regulation of epithelial-mesenchymal transition (EMT) process. Moreover, the human gene expression microarray clarified that MAPK/ERK pathway could be initiated by OR2T6 which was further identified by western blot analysis. So we proposed that OR2T6, as a novel oncogene, contributed to the progression of breast carcinoma by the initiation of EMT and MAPK/ERK pathway.